The Knowledge of Pulmonary Tuberculosis Among The Patients Under Tubercular Therapy in Teaching Hospital Dera Ghazi Khan - Leghari, Shazia Yasmeen; Parveen, Zubaida; Mukhtar, Madiha (Future Science, 2021)
Tuberculosis is a significant medical issue in numerous pieces of the world. For legitimate administration, learning about Tuberculosis is essential among the patients under anti-tubercular treatment. This study aimed to assess the knowledge and perception about Tuberculosis in the DHQ teaching hospital of Dera ghazi khan. This study is a cross-sectional descriptive research design. A self-reported questionnaire was filled by 100 registered patients of the antidote therapy program. Descriptive statistics were used to analyze the data. The results showed 68.80% male, and41.60% females have known about the treatment of Tuberculosis. 72.50% male,41.60% female have known the diagnosis. 41.33% male and 24.33% female have known about prevention.65% male, and47% females have known signs and symptoms of Tuberculosis. Conclusions included that males have more knowledge about Tuberculosis than females and common source of knowledge among patients in the hospital.